ANALISIS TINDAK PIDANA MILITER MURNI MENGENAI PENYALAHGUNAAN KEKUASAAN DALAM STUDI KASUS PUTUSAN No. 337 K/Mil/2022 - MUSA, ROSELA ISMAIL (Ganec Swara, 2025)
The main focus of this research is to analyze the judge’s consideration in handing down a verdict against a TNI Major involved in the crime of abuse of power. The method used in this research is a normative approach, which aims to explore the legal basis and juridical considerations used by the judge in this case. Pure military crimes, as regulated in the Military Criminal Code (KUHPM), are criminal acts that can only be committed by members of the military, and have special characteristics that distinguish them from general crimes. In the context of Decision No. 337 K/Mil/2022, the judge’s consideration included an analysis of the available evidence, as well as the impact of the defendant’s actions on the military institution and society. The results showed that the judge’s consideration was not only based on legal aspects, but also considered the values of justice and the social impact of the act. The judge attempted to uphold the principle of substantive justice by imposing appropriate sanctions, expected to provide a deterrent effect and maintain the integrity of military institutions. This research is expected to contribute to the understanding of military criminal law enforcement in Indonesia, especially in the context of abuse of power by members of the TNI.